Sonodecoration of magnetic phosphonated-functionalized sporopollenin as a novel green nanocomposite for stir bar sorptive dispersive microextraction of melamine in milk and milk-based food products. (30th March 2021) - Shirani, Mahboube; Kamboh, Muhammad Afzal; Akbari-adergani, Behrouz; Akbari, Ali; Sadia Arain, Sadaf; Rashidi Nodeh, Hamid
Graphical abstract: Highlights: Novel functionalized magnetic sporopollenin (MPSP) as an efficient sorbent. Stir bar sorptive dispersive microextraction (SBSDME) as a facile technique. Combination of SBSDME with MPSP for determination of trace levels of melamine. Successful application of the method in milk based food products as complex matrixes. Abstract: The novel green magnetic phosphonated-functionalized sporopollenin nanocomposite (MPSP-nanocomposite) was synthetized and used for stir bar sorptive dispersive microextraction (SBSDME) of melamine in milk and milk-based food products. TEM, SEM-EDX, FT-IR, VSM techniques were applied for characterization of MPSP-nanocomposite. The influential parameters including pH, extraction time, stirring rate, elution solvent type and volume, sample volume, desorption time, and ionic strength were studied and at optimum conditions, the linear range of 1–500 (µg L −1 ), the LOD (S/N = 3) of 0.30 (µg L −1 ), and the LOQ (S/N = 10) of 0.95 (µg L −1 ) were achieved. The intra-day precision values (RSD (%), n = 7) of 3.5% for the melamine concentration of 25 (µg L −1 ). The relative recoveries of 95.8% to 99.6% were acquired for the real samples which confirmed that the proposed method could be successfully utilized in complex matrixes with high matrix effects.